Genetic variability in Macrophomina phaseolina (Tassi.) Goid. incitant of Charcoal rot of maize in India - LOKENDRA SINGH and RAM DUTTA, MEENA SHEKHAR*, R.C. SHARMA, SUJAY RAKSHIT, POONAM YADAV (Indian Phytopathology, 2006)
Seven isolates of M. phaseolina incitant of maize charcoal rot were established from major maize growing agro-ecological zones of India. These isolates were analysed through RAPD marker for genetic diversity. The UPGMA cluster analysis for 706 loci score permitted identification of three main clusters. Similarity matrix and Jaccard’s similarity co-efficient between the isolates indicated that the maximum genetic variation was among isolates of Arabhavi and Coimbatore with 70.8% followed by Ludhiana and Coimbatore with 69.5%. The most closely related isolates were Hyderabad and Delhi with an affinity percentage of 65.5 followed by Udaipur and Bangalore isolate with a percentage of 62.9% similarity. Amplification of the ITS region with AD primers the entire ITS1 , rDNA and ITS2 region was amplified successfully for all the isolates studied. A single band of 750 bp was uniformally amplified in all the isolates and no polymorphism was visualized. Our results demonstrated genetic diversity among Indian isolates of M. phaseolina in maize.